(untitled) (Hekima Review, 2006)
Definitely, peace is an imperative reality in Africa. But the question is how many people choose to work for its realization? The contribution made by Elias Omondi Opongo, a Kenyan Jesuit, and Program officer for Peacebuilding at Jesuit Hakimani Centre in Nairobi, in his recent publication entitled Making Choice for an invitation to love. The aim of the book remains principally the deep desire of making peace a reality in conflict settings that, very often, are complex and perilous. Addressing the question of peace building, the author suggests that humanitarian organizations need to focus, not only on aid delivery, but also on actions that transform structures, which sustain conflict.